Changes in Soil Carbon Sequestration during Woody Plant Encroachment in Arid Ecosystems - Naikwade, P V (Plantae Scientia, 2021)
Carbon sequestration is one of the most important and highly recommended measures for mitigating climate change. Soil organic carbon (SOC) has potential to sequester the largest amount of carbon (C) for the longest time period in the midst of the organic C sinks in terrestrial ecosystems of the earth. In recent years, apprehension of the role of soils as sink for carbon on a wide-ranging scale has become dynamic. From last 150 years, encroachment of trees and shrubs into grasslands and the ‘thicketization’ of savannas have been reported and is a global phenomenon. One possibly beneficial effect could be that the shrub and tree-dominated ecosystems will sequester more carbon and will be a buffer for elevated atmospheric carbon dioxide (CO2) levels. The question of what is impact of woody encroachment on soil carbon balance of an ecosystem has proved difficult to answer, and the results remain debatable. The magnitude and pattern of changes in the SOC with woody encroachment are exceedingly abstruse and varies from significant increases, to significant decreases to no net change in SOC. Impact of wood plant encroachment on carbon sequestration is discussed in this paper considering various studies with different results so it will lead to better understanding of the complex phenomenon. SOC sequestration is effective greenhouse gas mitigation strategy and a vital ecosystem service. Increasing SOC may helpful to mitigate negative effects of growing concentration of CO2 in atmosphere and may be advantageous in decelerating or reversal in global climate change rate.